Volume 7: Turbomachinery, Parts A, B, and C 2011
DOI: 10.1115/gt2011-46054
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Suction-Side Winglet on Tip Leakage Flow in Compressor Cascade

Abstract: The effect of tip winglet on the aerodynamic performance of compressor cascade are mainly determined by the location of the tip winglet, the tip winglet geometry, the size of tip clearance, and the aerodynamic parameters of the cascade. In this paper, an extensive numerical study which includes three aspects has been carried out to investigate the effects of these influencing factors in a highly-loaded compressor cascade in order to give the guidance for the application of tip winglet to control the tip leakag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Although some investigation of tip winglet has been performed on compressor cascades and rotors, it is necessary to explore the detailed effects of winglet on flow characteristics and the stall margin of high loading compressor rotors in depth, especially focus on the characteristic variation of tip leakage flow caused by the effective installing location and size of winglet. 22 Therefore, the following problems will be discussed deeply in this article:…”
Section: Introductionmentioning
confidence: 99%
“…Although some investigation of tip winglet has been performed on compressor cascades and rotors, it is necessary to explore the detailed effects of winglet on flow characteristics and the stall margin of high loading compressor rotors in depth, especially focus on the characteristic variation of tip leakage flow caused by the effective installing location and size of winglet. 22 Therefore, the following problems will be discussed deeply in this article:…”
Section: Introductionmentioning
confidence: 99%
“…Although a few investigations of tip winglet on 2-D compressor cascades and low speed rotors have been performed, the detailed effects of winglet on flow characteristics and stall margin of high loading compressor rotors have not been illustrated clearly, and its application in compressor blades is also restricted inevitably. 23 Therefore, the following problems will be discussed in this paper:…”
Section: Introductionmentioning
confidence: 99%
“…Although a few investigations of tip winglet on 2-D compressor cascades and low speed rotors have been performed, the detailed effects of winglet on flow characteristics and stall margin of high loading compressor rotors have not been illustrated clearly, and its application in compressor blades is also restricted inevitably. 23 Therefore, the following problems will be discussed in this paper:The effects of winglet geometry on static pressure distribution and flow pattern near blade tip.How does different geometry size of tip winglet affect the mass flow rate and aerodynamic losses of leakage flow in tip region of a transonic rotor?The fundamental impacts of winglet geometry on overall performance and stall margin of transonic rotors.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it has been studied from a long time ago due to its immoderate loss on the compressor performance, and in particular, on the compressor performance in stall condition and researchers have tried to minimize the tip clearance loss by understanding the effects of tip clearance on the flow inside a compressor. Numerous methods such as implementing casing treatment (Kim et al, 2013), swept and leaned blades (Kroger et al, 2011), utilizing winglet on the suction side of blade Zhong et al, 2011) and using vertical impact jet (Bae et al, 2003) have been proposed to control the tip clearance flow and to achieve higher stability and better overall efficiency in the compressor. (Zhong et al, 2013) experimentally studied the effect of winglet on a cascade and concluded that the location of winglet has a considerable influence on the vortex produced as a result of blade tip leaked flow, and that the placement of winglet on the suction side proves effective in reducing the total outlet pressure and the secondary flow as a result of leakage flow from the tip clearance (Zhong et al, 2013).…”
Section: Introductionmentioning
confidence: 99%